2013
DOI: 10.3390/f4010085
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Microtopography and Nurse Canopy for Successful Restoration Planting of the Slow-Growing Conifer Pilgerodendron uviferum

Abstract: Abstract:Recent studies have shown that, owing to a lack of seed trees, the natural rate of recovery of fire-disturbed bog forests previously dominated by the endemic and endangered conifer Pilgerodendron uviferum (D. Don) Florin is extremely slow. Hence, increasing the number of seed trees in the landscape through restoration planting could remove the principal biotic filter, limiting recovery of these forests. Here, we analyzed how the success of restoration plantings may be improved through the choice or ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 37 publications
0
16
0
9
Order By: Relevance
“…Such deformations at the root collar could explain, at least partially, the higher root collar diameter of seedlings established after shrub removal in our experiment. Also, in upland conditions, Bannister et al () found that 2 years after planting, Pilgerodendron uviferum seedlings established in gaps had higher maximum rates of CO 2 assimilation, suggesting photosynthetic acclimation to high irradiance environments. However, these seedlings did not have higher growth rates (shoot and basal area growth).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such deformations at the root collar could explain, at least partially, the higher root collar diameter of seedlings established after shrub removal in our experiment. Also, in upland conditions, Bannister et al () found that 2 years after planting, Pilgerodendron uviferum seedlings established in gaps had higher maximum rates of CO 2 assimilation, suggesting photosynthetic acclimation to high irradiance environments. However, these seedlings did not have higher growth rates (shoot and basal area growth).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have highlighted the importance of monitoring the early performance of native species planted under different restoration techniques in degraded or burned forests (e.g. Bannister et al ; Donoso et al ; Soto et al , ). Many environmental variables can influence growth and survival in the early phases of tree development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…difieren en algunos aspectos con los presentados para el mismo ensayo por Bannister et al (2013) con 2 años de evaluación. Esto confirma la importancia de mantener este tipo de ensayos en el largo plazo.…”
Section: Enfoques De Restauraciónunclassified
“…Durante todos estos años se ha enfocado el trabajo en tres importantes aspectos relacionados a la restauración: a) entender los procesos ecológicos que ocurren en bosques turbosos inalterados, b) analizar el grado de recuperación natural de los bosques quemados, y c) explorar algunas opciones para su restauración. De este programa de investigación ha surgido información para diversas publicaciones científicas en los últimos años (Bannister, 2012;Bannister et al 2013Bannister et al , 2014Bannister et al 2012) y capítulos de libros (Lara et al 2013(Lara et al , 2014. En el presente trabajo se pretende resumir los principales resultados, experiencias, triunfos y fracasos tratando de estudiar y restaurar bosques alterados de P. uviferum.…”
Section: Introductionunclassified